A comparison of ten digestive enzymes reveals a lack of chitinase in a phasmid and the loss of two β‐glucanases in a mantid. (15th January 2020) - Woodring, Joseph
Abstract: In all developmental stages, the phasmid Peruphasma schultei (Conle & Hennemann, 2005) is an obligate herbivore, whereas the mantid Hierodula membranacea (Burmeister, 1838) is an obligatory carnivore. In P. schultei, the luminal activity of all enzymes is approxximately 50% in the crop and 50% in the midgut, which corresponds to the approximate 50 : 50 ratio of volumes of these two regions. These ratios would be expected in insects with a constant feeding rate on an unvaried diet. The enzyme activity and volume ratios in Hierodula membranacea vary considerably because of the irregular feeding habits. These differences in activity ratios between phasmids and mantids are not associated with the obligate phytophagous or carnivorous diet. The ratio of membrane bound to luminal aminopeptidases and disaccharidases in the midgut of both species are not significantly different and are within the normal range of other paurometabolous insects. Cellobiase and other plant cell wall digesting enzymes, laminarinase and cellobiase, are present in the phasmid but totally lacking in the mantid. The obligate carnivorous feeding habits of mantids could represent a selective factor leading to the loss of the ability to produce β‐glucanases. Chitinase is a moulting enzyme in all insects, whereas, in H. membranacea, chitinase also occurs as a luminal digestive enzyme. This modified enzyme function requires production and secretion in another tissue, namely the midgut. Abstract : The low nutrient value of plant foods favours reduced total enzyme activity in the midgut of phasmids. The ratio of bound to unbound enzymes is not correlated with the diet of the phasmid or mantid. The phasmid Peruphasma schultei is an obligatory leaf eater and secretes cell wall digesting enzymes in the midgut. The mantid Hierodula membranacea is an obligatory carnivore, lacks plant wall digestive β‐glucanases and secretes a digestive chitinase in the midgut.